Anxiety at The Continued Age of High Risk Towards Plague Transmission in The 2019 Coronavirus Disease Pandemic - Marina Dwi Mayangsari; Dwi Nurrachmah; Alvina Rizkiani; Alda Nursyifa Aidilla; Tuti Asmaniah (Lambung Mangkurat, 2021)
The elderly are very vulnerable to anxiety, especially during the Covid-19 pandemic. Many elderly people are infected with this virus, especially those who have comorbids. The feeling of worrying about mortality rate raises the risk of physical condition decreasing, this further increases susceptibility to infection. This study aims to determine the description and the factors that cause anxiety. The study was conducted using a qualitative approach. Data collection methods used observation, interviews, and Geriatric Anxiety Scale (GAS). The research subjects for the initial survey were five people, then deepening to an elderly woman (BW), 63 years old who obtained the highest anxiety score. The results showed that the elderly felt anxious about their surroundings being exposed to the Covid-19 virus, it’s seen from the symptoms such as restlessness, difficulty sleeping, and disturbed concentration of thought. Anxiety is caused by physical factors such as suffering from accompanying illness, trauma from emotional experiences, and loss contact with the social environment. The conclusion that the elderly excessive worry because of their physical vulnerability so they often worried if they contracted Covid-19. Simple intervention suggestions such as remembrance therapy in order to calm the feelings and thoughts of the subject during the Covid-19 pandemic.